2009
DOI: 10.1159/000222780
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association between the Level of High-Sensitivity C-Reactive Protein and Idiopathic Parkinson’s Disease? A Comparison of Parkinson’s Disease Patients, Disease Controls and Healthy Individuals

Abstract: Background: High-sensitivity C-reactive protein (hs-CRP) is a sensitive systemic marker of inflammation, and increased levels of hs-CRP are associated with inflammatory reactions. Microglia-mediated neuroinflammation has been hypothesized to play an important role in the pathogenesis of idiopathic Parkinson’s disease (PD). However, the clinical value of hs-CRP in PD is poorly defined. Therefore, we conducted this study to investigate the clinical value of hs-CRP in patients with PD. Methods: We examined 212 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 79 publications
2
48
2
Order By: Relevance
“…A similar result has been observed in another study, which demonstrated an elevated serum CRP in PD and ischemic cerebrovascular disease compared to control subjects [6]. It has been documented that the plasma concentration of Hcy is elevated in PD patients, and this increase is associated with the long-term effects of chronic or acute administration of L-dopa [7,8,9,10].…”
Section: Introductionsupporting
confidence: 85%
“…A similar result has been observed in another study, which demonstrated an elevated serum CRP in PD and ischemic cerebrovascular disease compared to control subjects [6]. It has been documented that the plasma concentration of Hcy is elevated in PD patients, and this increase is associated with the long-term effects of chronic or acute administration of L-dopa [7,8,9,10].…”
Section: Introductionsupporting
confidence: 85%
“…The pathogenesis of PDD and PD is currently unknown; however, at the cellular level, significant microglial inflammation is observed in regions of dopaminergic degeneration, and some protection against PD is offered by the long-term administration of anti-inflammatory medications (6,18). In addition, microglia-mediated neuroinflammation has been hypothesized to play an important role in the pathogenesis of PD as well as in the cognitive decline observed in patients with AD (6,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, microglia-mediated neuroinflammation has been hypothesized to play an important role in the pathogenesis of PD as well as in the cognitive decline observed in patients with AD (6,19,20). The large number of recent reviews on the subject bears witness to the growing realization of the importance of the inflammatory response in the progression of PD, a hypothesis that has received strong sup- .951); however, significant differences were observed between the normal controls and both groups of PD patients (p=0.020 and 0.048 for the PDwoD and PDD groups, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical data reviewed in Section 3 of this manuscript further demonstrates that the GBMAx may be a source of this systemic inflammatory response. 161 . Further, longitudinal epidemiological data suggests that chronic systemic inflammation often precedes the onset of these conditions and therefore, is a likely risk factor [162][163][164] .…”
Section: Potential Clinical Implicationsmentioning
confidence: 99%